Electrical Nucleotide Sensor Based on Synthetic Guanine‐Receptor‐Modified Electrodes. Issue 13 (6th April 2018) - Ohshiro, Takahito; Verma, Rajiv Kumar; Yokota, Kazumichi; Tsutsui, Makusu; Mukherjee, Sanjukta; Kawai, Tomoji; Nakatani, Kazuhiko; Taniguchi, Masateru
Abstract: Methyl 2‐carbamate‐1, 8‐naphthyridine thiophenolate derivative (NCTP) has been designed and synthesized, which can selectively bind to guanine derivatives. We immobilized NCTP on gold electrode and performed cyclic voltammetry analysis for guanosine sensing. The current blockage data obtained from these NCTP immobilized electrodes suggest that electrodes have higher selectivity for 2'‐deoxyguanosine monophosphate (dGMP) than 2'‐deoxythymidine monophosphate (dTMP), 2'‐deoxycytidine monophosphate (dCMP), and 2'‐deoxyadenosine monophophate (dAMP). Thus, synthetic reader molecule NCTP, which has complementary hydrogen bonding surface for guanine derivatives, could be useful for the sensing of guanosine mononucleotides and polynucleotides. Abstract : Ligand immobilized dGMP sensor: A potential guanine sensor molecule has been reported. The ligand with 1, 8‐naphthyridine carbamate (NC) moiety has been synthezised and immobilized on the gold electrode. This electrode showed high selectivity for guanine derivatives due to complementary hydrogen bonding surfaces provided by NC moieties on the electrode surface.